INTERNET OF THINGS (IOT) IN SCHOOLS: IMPROVING THE EFFICIENCY AND QUALITY OF EDUCATION - Alim Hardiansyah; Rita Hayati; Sufia Widi Kasetyaningsih (Adisam Publisher, 2026)
The implementation of the Internet of Things (IoT) in the school environment promises a significant transformation in improving the efficiency and quality of education. IoT technology enables the creation of a more interactive and personalised teaching-learning process, providing an educational experience that is better suited to the needs of individual students. In addition, IoT helps teachers monitor student progress in real-time, enabling more effective intervention and assistance. In terms of school management, IoT makes it easier to automate various operational tasks such as inventory control, energy management, and facilities maintenance, all of which contribute to cost savings and improved learning environments. However, successful implementation of IoT requires adequate technological infrastructure as well as special attention to privacy and data security issues. Therefore, cooperation between various stakeholders is necessary to overcome these challenges and maximise the potential of IoT in education.